इष्टदेव झूलेलाल - Lakshman Parasram Hardwani (Sindhi Sewa Mandal, Savedi, Ahmadnagar, Maharashtra, 2012)
Ishtdev Jhulelal is a folk literature in Sindhi language.
Ishtdev Jhulelal
Keywords: Sindhi; इष्टदेव झूलेलाल; Ishtdev Jhulelal; Folk Literature; Sindhi; Sindhi